Simulation on coupling effects between surface wear and fatigue in spur gear. (April 2022) - Yan, Yutao; Jiang, Cheng; Li, Wendong
Highlights: The behavior of spur gear under wear-fatigue coupling is investigated. A simple life prediction model for wear-fatigue coupling is established. The relationship between the equivalent stress intensity factor at the crack tips and the crack propagation rate under coupling effect is determined. The effects of surface wear on crack propagation, service life and failure mode are analyzed. Abstract: A surface wear prediction method is used to determine the wear rate of the tooth surface. This method employs the Archard's wear model together with the gear contact mechanics model. An equivalent calculation model based on Hertzian contact theory and fracture mechanics is used to investigate crack initiation and crack propagation. The virtual crack extension (VCE) method is employed to analyze the propagation process from the initial crack to occurrences of tooth surface pitting. A life prediction method on the wear-fatigue coupling is developed. The crack propagation process and pit shapes are determined by the iterative analysis. The relationship between service life and the remaining distance from the crack tips to the tooth surface is determined. The damage mechanism of wear-fatigue coupling is explored. The results of the comparative analysis show that the wear of tooth surface affects the cracks propagation characteristics, reduces the service life and even can change the failure mode. The simulated pit shapes and crack propagation process are in good agreement with the results of other literature. The analysis method of wear-fatigue coupling damage can well simulate the damage process and predict service life in spur gear.